Particle gel material with improved strength and preparation method thereof
By introducing electrospinning 3D printing nano-fiber scaffolds prepared by electrospinning into traditional hydrogel materials and filling the particle gel into the scaffold, the problem of insufficient mechanical properties of traditional hydrogel materials is solved, and the mechanical strength, flexibility and stability of the material is significantly improved, and it is suitable for multifunctional applications.
Patent Information
- Application Number
- CN202411887527.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
AI Technical Summary
Traditional hydrogel materials have insufficient mechanical properties in actual applications and cannot meet the needs of scenarios that require higher strength.
Electrospinning 3D printing technology is used to prepare nano-microfiber scaffolds, and the particle gel is filled into the scaffolds, forming a monolithic material through the polymerization of hydrogels.
It significantly improves the mechanical strength, flexibility and stability of the material, and is suitable for flexible wearable devices, environmental monitoring and other fields.
Smart Images

Figure CN119592032A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of material science and bioengineering, and in particular to a particle gel material with improved strength and a preparation method thereof, which is particularly suitable for the fields of biocompatible materials, biosensors, mechanical manufacturing, etc. Background Art
[0002] As a common matrix material for particle gel, hydrogel is widely used due to its excellent biocompatibility and water absorption. However, traditional hydrogels have significant mechanical performance deficiencies in practical applications and cannot meet the needs of certain scenarios that require higher strength. Therefore, improving the mechanical properties of hydrogel materials has become a research focus. At present, common improvement methods include: increasing polymer concentration, increasing cross-linking density, or incorporating nanoparticles such as hydroxyapatite and silica into hydrogels. Although these methods can improve the strength of hydrogels to a certain extent, they often face the problems of reduced flexibility or limited functionality.
[0003] In order to further enhance the overall performance of the particle gel material, researchers began to try to introduce structural reinforcement parts, such as constructing nano-micron fiber scaffolds through 3D printing, electrospinning and other technologies. This scaffold has high strength, excellent flexibility and porous structure, which can effectively fill the particle gel and improve the overall mechanical properties and stability of the material. The nano-micron fiber scaffold is prepared by electrospinning 3D printing. The unique arrangement and porous structure of its nano-scale fibers not only provide a stable support for the particle gel, but also allow substances in the external environment (such as gas and liquid) to enter and exit freely, thus taking into account the functionality and mechanical strength of the material. In addition, using hydrogel as a fixing material, the particle gel can be combined with the nano-micron fiber scaffold to form an integral material through polymerization. This composite material not only solves the problem of poor mechanical properties of hydrogel, but also maintains its excellent flexibility and functionality, showing great application potential. Compared with traditional particle gel materials, the composite structure has significantly improved mechanical properties, stability and applicability.
[0004] CN2023103764444 discloses a method for enhancing the efficiency of filtering particulate matter in the air by strengthening electrospinning membrane using sludge extract. The present invention uses nylon as the main spinning component, and incorporates sludge extract in the electrospinning process. The rich functional groups contained in the sludge extract can enhance the capture of polar particulate matter by the fiber, which is a new high-value utilization of solid waste "sludge". Using sludge extract to manufacture mask filter membranes can not only meet the demand for masks, but also recycle a large amount of accumulated residual sludge solid waste.
[0005] CN201710073060X relates to an electrospinning method for preparing a fiber membrane with a three-dimensional structure, which uses a receiving electrode with a three-dimensional structure including protrusions and perforations. The method of the present invention can produce fiber membranes with different fiber membrane thicknesses and different fiber arrangement densities. The fiber film with a three-dimensional structure has a simple preparation method, low cost, and is suitable for industrial production. The prepared nanofiber membrane has excellent air permeability and water permeability. It has high interception efficiency for particulate matter in the air. As a water filter material, it has high flux and high retention rate.
[0006] CN201810021835.3 relates to a composite scaffold material based on electrospun yarn and hydrogel and a preparation method thereof. The preparation method of the composite scaffold material comprises the following steps: preparing a type I collagen solution; providing an electrospun yarn, placing the electrospun yarn in the type I collagen solution, and then obtaining the composite scaffold material after the type I collagen solution becomes a gel.
[0007] CN201810447677.8 discloses a method for preparing highly absorbent 3D nanofiber aerogel by electrospinning and the resulting material, the method comprising the following steps: (1) using amphiphilic block copolymer mPEG-PCL as raw material, dissolving it in a mixed solvent, preparing nanofibers by electrospinning, and collecting nanofiber membranes; (2) dispersing the nanofiber membranes in water; (3) freeze-drying the dispersed nanofiber liquid; (4) heating and cross-linking the freeze-dried sample to prepare the highly absorbent 3D nanofiber aerogel.
[0008] However, it does not involve the application of special particle gels as high-performance flexible sensors in the field of wearable devices, as functional materials for drug release platforms and environmental monitoring. Therefore, the development of a high-strength material based on nano-micron fiber scaffolds and particle gel composites can not only effectively improve the structural properties of particle gels, but also provide new solutions for flexible wearable devices, environmental monitoring and other fields. Summary of the invention
[0009] Purpose of the invention: The present invention aims to provide a particulate gel material with enhanced mechanical structure to overcome the problem of insufficient mechanical strength of traditional hydrogel materials and improve their application performance in the fields of flexible wearable devices, environmental monitoring, etc. In addition, the present invention also provides a method for efficiently preparing the material to ensure that it has excellent mechanical strength, flexibility and applicability.
[0010] The technical solution of the present invention is: a particle gel material with improved strength, comprising a structural reinforcement part and a particle gel part; the structural reinforcement part is a nano-micron fiber scaffold prepared by electrospinning 3D printing technology, and the particle gel part fixes the particle gel in the nano-micron fiber scaffold through hydrogel, and makes it a whole through polymerization of hydrogel;
[0011] The precursor solution or melt required for the particle gel is a mixture of one or more of the polymer materials selected from polycaprolactone, polylactic acid, polylactic acid-glycolic acid copolymer, chitosan, silk fibroin, polyethylene oxide, polyvinyl alcohol, polyurethane, and polystyrene; or a mixture of one or more of the materials and silicon dioxide or hydroxyapatite nanoparticles.
[0012] The method for preparing the particle gel material with improved strength comprises the following steps:
[0013] (1) preparing a nano-micron fiber scaffold, preparing a solution or melt required for electrospinning 3D printing, and performing electrospinning 3D printing, and stacking the obtained micron or nanofibers layer by layer to form a nano-micron fiber scaffold that can be filled with particle gel and hydrogel materials;
[0014] (2) Preparing a precursor solution for particle gel to construct particle gel; the precursor solution of the particle gel is a natural polymer solution, such as one or more of gelatin, sodium alginate, hyaluronic acid, cellulose and their derivatives; or a synthetic polymer solution, such as one or more of acrylamide and hydroxyethyl methacrylate; or a mixed solution of a natural polymer solution and a synthetic polymer solution.
[0015] (3) Filling and polymerization: preparing a hydrogel precursor solution, mixing it with the particle gel, and filling it into the nano-micron fiber scaffold to obtain the particle gel material under polymerization conditions; after the precursor solution is mixed with the particle gel loaded with functional substances, it is filled into the nano-micron fiber scaffold and polymerized to form an integral material.
[0016] In step (2), a precursor solution required for the particle gel is prepared, and the particle gel is prepared by batch emulsification, microfluidics, photolithography, electrohydrodynamic spraying or mechanical crushing. Specifically, a particle gel precursor solution is prepared, and then the particle gel is formed by solidification, or a large block of hydrogel is crushed into the particle gel.
[0017] In step (1), the electrospinning 3D printing is to spin the above-mentioned solution or melt in a strong electric field and 3D print it, and stack the obtained micron or nanofibers layer by layer to form a nano-micron fiber scaffold that can be filled with particle gel and hydrogel materials.
[0018] In step (2), the constructed particle gel is a spherical particle that immobilizes one or more substances; according to the fixed functional substances, it can be used as a sensor to respond to external signals such as external chemical molecules, biological molecules, temperature, humidity, pressure, etc., and perform feedback behaviors, such as expressing fluorescence, physical color change, etc.
[0019] In step (3), the fixation method for solidifying to form a biocompatible hydrogel block includes chemical crosslinking, free radical polymerization, click chemical crosslinking, Schiff base formation or disulfide formation; or physical crosslinking guest-host interaction, hydrogen bonding, metal-ligand coordination or ionic crosslinking; or chemical and physical double crosslinking.
[0020] In step (3), the hydrogel precursor solution is a solution that can be cured to form a biocompatible hydrogel block, including a natural polymer solution (such as one or more of gelatin, sodium alginate, hyaluronic acid, cellulose and its derivatives); or a synthetic polymer solution (such as one or more of acrylamide, hydroxyethyl methacrylate); or a mixed solution of the natural polymer solution and the synthetic polymer solution. After the precursor solution is mixed with the particle gel, it is filled in the nano-micron fiber scaffold and polymerized to form an integral material.
[0021] The present invention dopes the particle gel into the electrostatic spinning grid to form a composite structure material. Due to the porosity and functionalization characteristics of the particle gel, it can be used as a drug-carrying substrate.
[0022] However, the application of particle gel lacks a good base material that can carry the particle gel. Since the electrospinning structure provides excellent air permeability and flexibility, it is suitable for making comfortable materials that can be worn for a long time, such as the underlying support of smart patches.
[0023] Therefore, the combination of particle gel and grid enhances functionality. The core of this patent is to improve the mechanical properties that gel particles alone do not have; particle gel and block gel are filled into the scaffold network to enhance the strength of the gel.
[0024] Depending on the particle gel carried, the present invention can be used as a high-performance flexible sensor and drug release platform in the field of wearable devices; in the field of environmental monitoring, it can be used for efficient gas and liquid filtration, or as a functional material for pollutant detection. Compared with traditional technologies, the present invention significantly improves the mechanical properties, adsorption properties and stability of the material through the composite design of electrospinning grid and particle gel, providing an innovative solution for multifunctional applications.
[0025] Beneficial effects: Compared with the prior art, the present invention has the following effects:
[0026] (1) Improved mechanical properties:
[0027] The addition of nano-micron fiber scaffolds significantly improves the mechanical strength of the material, enabling it to perform well in scenarios such as flexible wearable devices and environmental monitoring that require both flexibility and strength, especially in the field of biological monitoring.
[0028] (2) Functionality of particle gel:
[0029] The introduction of particle gel not only provides functional plasticity of the material, but also significantly improves the overall stability of the material and reduces the risk of particle shedding or leakage during use.
[0030] (3) Simple process and environmentally friendly:
[0031] The preparation method is simple to operate, green and environmentally friendly, uses materials with good biocompatibility, is low in cost and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the SEM image of the nano-micron fiber scaffold in Example 1;
[0033] Figure 2 The nano-micron fiber scaffold in Example 1;
[0034] Figure 3 This is a schematic diagram of the particle gel microspheres in Example 1;
[0035] Figure 4 The particle gel material with improved strength in Example 1;
[0036] Figure 5 This is a stress-strain comparison diagram of the nano-micron fiber reinforced particle gel material and the pure particle gel material in Example 1.
[0037] Figure 6 This is a comparison chart of the tensile properties of the nano-micron fiber reinforced particle gel material and the pure particle gel material in Example 1.
[0038] Figure 7 This is a diagram of the patterned fiber scaffold in Example 1.
[0039] Figure 8 This is the biosensor detection diagram in Example 5. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with specific embodiments.
[0041] Example 1
[0042] Particle gel material with enhanced strength: Structural reinforcement part: Nano-micron fiber scaffold prepared by electrospinning 3D printing technology, which has high mechanical strength and porous structure and can serve as the skeleton support of the whole material. Particle gel part: filled in the nano-micron fiber scaffold, fixed to the scaffold by hydrogel, and the two parts are combined into a whole by polymerization of hydrogel. The details are as follows
[0043] (1) Electrospinning 3D Printing Polymer Nano-Micro Fiber Scaffold
[0044] Weigh 950mg PCL particles and 50mg PLGA powder, shake and mix them, put them into the 3D printing needle barrel, turn on the computer, set the parameters of the electric field to 5KV, the syringe heating temperature to 75℃, the needle heating temperature to 95℃, adjust the distance between the needle and the platform to 2.5mm, set the voltage to 4.5kv, the air pressure to 13kpa, set the bracket length to 20mm, the width to 20mm, the grid spacing to 0.8*0.8mm, the number of layers to 100, and the printing speed to 1500mm / min. After the settings are completed, first click Extrude to allow it to stabilize the filament. After it stabilizes, click Print, and the machine will automatically print until it is completed. The printed nano-micron fiber scaffold is shown below. Figure 1 , 2 , 6, and 7.
[0045] (2) Preparation of loaded particle gel microspheres with hyperbranched polyethylene glycol diacrylate (HB-PEGDA) and dextran (Dex)
[0046] The surfactant (FE-surf) was dissolved in fluorinated oil to prepare a mass fraction of 2%, which was recorded as the continuous phase P1 (oil phase); 200 mg HB-PEGDA was dissolved in 1 mL deionized water to prepare 20% (w / v), which was recorded as the dispersed phase P2; 200 mg dextran and 100 μL of Escherichia coli with green fluorescent protein were dissolved in deionized water to prepare 20% (w / v), which was recorded as the dispersed phase P3; the above prepared solution was connected to the microfluidic chip through a PET pipe; the flow rate of the P1 oil phase was adjusted to 20 μL / min, the flow rate of P2 was 2 μL / min, and the flow rate of P3 was 0.5 μL / min, the microspheres were collected for 1 hour, blue light was cured for 50 seconds, and the particle gel microspheres were washed out, such as Figure 3 shown.
[0047] (3) Preparation of particle gel materials with improved strength
[0048] Weigh 150 mg of double bond gelatin (Gel-MA) and dissolve it in 1.5 mL of deionized water to make 10% (w / v), which is recorded as P5; weigh 7.5 mg of LAP blue light initiator and add it to P5 to dissolve, which is recorded as P6; mix the washed microspheres with the P6 solution, which is recorded as P7; place the nano-micron fiber scaffold in a plastic culture dish, pour P7 into the nano-micron fiber scaffold, and then blue light cure for 100 seconds. The prepared particle gel material with enhanced strength is shown in Figure 1. Figure 4 shown.
[0049] Example 2
[0050] (1) Electrospinning 3D Printing Polymer Nano-Micro Fiber Scaffold
[0051] Weigh 1g PCL particles and put them into the 3D printing needle barrel. Turn on the computer and set the parameters. The syringe heating temperature is 65℃, the needle heating temperature is 85℃, the distance between the needle and the platform is adjusted to 2.5mm, the voltage is set to 5kv, the air pressure is set to 15kpa, the bracket length is set to 20mm, the width is set to 20mm, the grid spacing is set to 0.8*0.8mm, the number of layers is set to 100, and the printing speed is set to 1500mm / min. After the settings are completed, click Extrude first to allow it to stably produce filaments. After it is stable, click Print, and the machine will automatically print until it is completed.
[0052] (2) Preparation of particle gel microspheres by double bond F127 (F127-DA) and dextran (Dex)
[0053] The surfactant (FE-surf) was dissolved in fluorinated oil to prepare a mass fraction of 2%, which was recorded as the continuous phase P1 (oil phase); 150 mg F127-DA was dissolved in 1 mL deionized water to prepare 15% (w / v), and then 5 mg LAP blue light initiator was weighed and dissolved in the above solution, which was recorded as the dispersed phase P2; 40 mg Dex was dissolved in deionized water to prepare 4% (w / v), which was recorded as the dispersed phase P3; the solution prepared above was connected to the microfluidic chip through a PET pipe; the flow rate of the P1 oil phase was adjusted to 20 μL / min, the flow rate of P2 was 2 μL / min, and the flow rate of P3 was 2 μL / min. The collected microspheres were blue-light cured for 50 s, and the gel microspheres were washed out.
[0054] (3) Preparation of particle gel materials with improved strength
[0055] Weigh 150 mg of double bond gelatin (Gel-MA), dissolve it in 1.5 mL of deionized water to make it 10% (w / v), recorded as P4; weigh 7.5 mg of LAP blue light initiator, add it to P4 and dissolve it, recorded as P5; mix the washed microspheres with the P5 solution, recorded as P6; place the fiber scaffold in a plastic culture dish, pour P6 into the fiber scaffold, and then blue light cure for 100 seconds.
[0056] Example 3
[0057] (1) Electrospinning 3D Printing Polymer Nano-Micro Fiber Scaffold
[0058] Weigh 950mg PCL particles and 50mg PLGA powder, shake and mix them, put them into the 3D printing needle barrel, turn on the computer, set the parameters, syringe heating temperature 75℃, needle heating temperature 95℃, adjust the distance between the needle and the platform to 2.5mm, set the voltage to 4.5kv, the air pressure to 13kpa, set the bracket length to 20mm, the width to 20mm, the grid spacing to 0.8*0.8mm, the number of layers to 100, and the printing speed to 1500mm / min. After the settings are completed, click Extrude first to allow it to stably produce filaments. After it stabilizes, click Print, and the machine will automatically print until it is completed.
[0059] (2) Preparation of double bond gelatin (Gel-MA) particle gel microspheres
[0060] The surfactant (FE-surf) was dissolved in fluorinated oil to prepare a mass fraction of 2%, which was recorded as the continuous phase P1 (oil phase); 80 mg of Gel-MA was dissolved in 1 mL of deionized water to prepare 8% (w / v), which were recorded as dispersed phases P2 and P3; the solutions prepared above were connected to the microfluidic chip through a PET pipe; the flow rate of the P1 oil phase was adjusted to 40 μL / min, and the flow rate of P2 was adjusted to 4 μL / min, the microdroplets were collected, blue light cured for 50 s, and the microspheres were washed out.
[0061] (3) Preparation of particle gel materials with improved strength
[0062] Weigh 7.5 mg of LAP blue light initiator, add it to P3 to dissolve, record it as P4; mix the washed microspheres with the P4 solution, record it as P5; place the fiber scaffold in a plastic culture dish, pour P5 into the fiber scaffold, and then blue light cure for 100 seconds.
[0063] Example 4
[0064] (1) Electrospinning 3D Printing Polymer Nano-Micro Fiber Scaffold
[0065] Weigh 950mg PCL particles and 50mg PLGA powder, shake and mix them, put them into the 3D printing needle barrel, turn on the computer, set the parameters, syringe heating temperature 75℃, needle heating temperature 95℃, adjust the distance between the needle and the platform to 2.5mm, set the voltage to 4.5kv, the air pressure to 13kpa, set the bracket length to 20mm, the width to 20mm, the grid spacing to 0.8*0.8mm, the number of layers to 100, and the printing speed to 1500mm / min. After the settings are completed, click Extrude first to allow it to stably produce filaments. After it stabilizes, click Print, and the machine will automatically print until it is completed.
[0066] (2) Preparation of particle gel microspheres by hyperbranched polyethylene glycol diacrylate (HB-PEGDA) and thiolated sodium alginate (SH-SA)
[0067] The surfactant (FE-surf) was dissolved in fluorinated oil to prepare a mass fraction of 2%, which was recorded as the continuous phase P1 (oil phase); 20 mg SH-SA was dissolved in 1 mL deionized water to prepare 2% (w / v), which was recorded as the dispersed phase P2; 100 mg HB-PEGDA solution was dissolved in deionized water to prepare 10% (w / v), which was recorded as the dispersed phase P3; 100 mg HB-PEGDA solution was dissolved in deionized water to prepare 10% (w / v), which was recorded as the dispersed phase P4; the solutions prepared above were connected to the microfluidic chip through a PET pipe; the flow rate of the P1 oil phase was adjusted to 20 μL / min, the flow rate of P2 was 2 μL / min, and the flow rate of P3 was 2 μL / min. The samples were collected for half an hour, the P3 solution was replaced with P4, and the samples were collected for another half an hour. The microspheres were collected for a total of 1 hour, and the microspheres were solidified and the particle gel microspheres were washed out.
[0068] (3) Preparation of particle gel materials with improved strength
[0069] Weigh 150 mg of double-bond modified hyaluronic acid, dissolve it in 1.5 mL of deionized water to make 10% (w / v), recorded as P5; weigh 7.5 mg of LAP blue light initiator, add it to P5 and dissolve it, recorded as P6; mix the washed microspheres with the P6 solution, recorded as P7; place the fiber scaffold in a plastic culture dish, pour P7 into the fiber scaffold, and then blue light cure for 100 seconds.
[0070] Example 5
[0071] The mechanical properties of the nano-micron fiber reinforced composite scaffold of the present invention were investigated, and two groups of experiments were designed: Group 1 was a nano-micron fiber reinforced composite scaffold, which consisted of micro-nano fibers, particle gel and hydrogel, and the preparation process was the same as that in Example 1, and was recorded as GelMA-95% PCL+5% PLGA; Group 2 was a pure particle gel and hydrogel, which was a pure hydrogel material prepared by the prior art, consisting of particle gel and hydrogel, and the preparation process was the same as that in Example 1, and was recorded as GelMA; The two particle gel materials were subjected to compression tests, and the results were as follows: Figure 5 As shown in FIG. 1 , due to the addition of the nano-micron fiber scaffold, the mechanical properties of the particle gel material with improved strength in the present invention are much higher than those of the ordinary particle gel material. The tensile properties of the two particle gel materials were tested, and the results are shown in FIG. Figure 6 As shown, due to the addition of the nano-micron fiber scaffold, the tensile strength of the particle gel material with improved strength in the present invention is much higher than that of the common particle gel material.
[0072] Example 6
[0073] (1) Electrospinning 3D Printing Polymer Nano-Micro Fiber Scaffold
[0074] Weigh 950mg PCL particles and 50mg PLGA powder, shake and mix them, put them into the 3D printing needle barrel, turn on the computer, set the parameters, syringe heating temperature 75℃, needle heating temperature 95℃, adjust the distance between the needle and the platform to 2.5mm, set the voltage to 4.5kv, the air pressure to 13kpa, set the bracket length to 20mm, the width to 20mm, the grid spacing to 0.8*0.8mm, the number of layers to 100, and the printing speed to 1500mm / min. After the settings are completed, click Extrude first to allow it to stably produce filaments. After it stabilizes, click Print, and the machine will automatically print until it is completed.
[0075] (2) Preparation of double bond gelatin (Gel-MA) particle gel microspheres and loading of responsive Escherichia coli
[0076] Escherichia coli with red fluorescent protein that responds to IPTG were added to LB culture medium, activated at 37°C for 12 hours, and the bacterial solution was diluted to an OD600 value between 0.6 and 0.8; the surfactant (FE-surf) was dissolved in fluorinated oil to prepare a mass fraction of 2%, which was recorded as the continuous phase P1 (oil phase); 80 mg of Gel-MA was dissolved in 1 mL of deionized water to prepare 8% (w / v), and mixed with 100 μL of bacterial solution, which was recorded as the dispersed phase P2; the solution prepared above was connected to the microfluidic chip through a PET pipe; the flow rate of the P1 oil phase was adjusted to 40 μL / min, and the flow rate of P2 was adjusted to 4 μL / min, and the microspheres collected for a total of 1 hour were blue-light cured for 50 seconds, and the microspheres were washed out.
[0077] (3) Preparation of particle gel materials with improved strength
[0078] Weigh 7.5 mg of LAP blue light initiator, add it to P3 to dissolve, record it as P4; mix the washed microspheres with the P4 solution, record it as P5; place the fiber scaffold in a plastic culture dish, pour P5 into the fiber scaffold, and then blue light cure for 100 seconds.
[0079] (4) Structural enhanced biological living sensing materials for biosensing
[0080] The prepared enhanced biological living material was cultured at 37°C with shaking. Escherichia coli with red fluorescent protein responded to IPTG and expressed red fluorescent protein, which could be clearly observed at an emission wavelength of 545. The IPTG solution was applied to the surface of the arm and the fiber scaffold patch was attached. The results were as follows: Figure 8 As shown, red fluorescence can be observed within 10 minutes, proving the sensitivity and practicality of the biological patch detection.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A particle gel material with improved strength, characterized in that: It includes a structural reinforcement part and a particle gel part; the structural reinforcement part is a nano-micron fiber scaffold prepared by electrospinning 3D printing technology, and the particle gel part fixes the particle gel in the nano-micron fiber scaffold through hydrogel, and makes it a whole through the polymerization of hydrogel; The precursor solution or melt required for the particle gel is a mixture of one or more of the polymer materials selected from polycaprolactone, polylactic acid, polylactic acid-glycolic acid copolymer, chitosan, silk fibroin, polyethylene oxide, polyvinyl alcohol, polyurethane, and polystyrene; or a mixture of one or more of the materials and silicon dioxide or hydroxyapatite nanoparticles.
2. The method for preparing a granular gel material with improved strength as claimed in claim 1, characterized in that: The following steps are involved: (1) preparing a nano-micron fiber scaffold, preparing a solution or melt required for electrospinning 3D printing, and performing electrospinning 3D printing, and stacking the obtained micron or nanofibers layer by layer to form a nano-micron fiber scaffold that can be filled with particle gel and hydrogel materials; (2) preparing a precursor solution required for particle gel to construct particle gel; the precursor solution of the particle gel is a natural polymer solution, such as one or more of gelatin, sodium alginate, hyaluronic acid, cellulose and its derivatives; or a synthetic polymer solution, such as one or more of acrylamide and hydroxyethyl methacrylate; or a mixed solution of a natural polymer solution and a synthetic polymer solution; (3) filling and polymerization, preparing a hydrogel precursor solution, mixing it with the particle gel, and filling it into the nano-micron fiber scaffold to obtain the particle gel material under polymerization conditions; The precursor solution is mixed with the particle gel loaded with functional substances, filled in the nano-micron fiber scaffold and polymerized to form an integral material.
3. The method for preparing a granular gel material with improved strength according to claim 2, characterized in that: In step (2), a precursor solution required for the particle gel is prepared, and the particle gel is prepared by batch emulsification, microfluidics, photolithography, electrohydrodynamic spraying or mechanical crushing. Specifically, a particle gel precursor solution is prepared, and then the particle gel is formed by solidification, or a large block of hydrogel is crushed into the particle gel.
4. The method for preparing a granular gel material with improved strength according to claim 2, characterized in that: In step (1), the electrospinning 3D printing is to spin the above-mentioned solution or melt in a strong electric field and 3D print it, and stack the obtained micron or nanofibers layer by layer to form a nano-micron fiber scaffold that can be filled with particle gel and hydrogel materials.
5. The method for preparing a granular gel material with improved strength according to claim 2, characterized in that: In step (2), the constructed particle gel is a water particle of regular or irregular shape such as sphere, cube, or cuboid, and one or more substances are immobilized; according to the functional substances immobilized, it can be used as a sensor to respond to external signals such as external chemical molecules, biological molecules, temperature, humidity, pressure, etc., and respond to feedback behaviors such as expressing fluorescence, physical color change, etc.
6. The method for preparing a granular gel material with improved strength according to claim 2, characterized in that: In step (3), the fixation method for solidifying to form a biocompatible hydrogel block includes chemical crosslinking, free radical polymerization, click chemical crosslinking, Schiff base formation or disulfide formation; or physical crosslinking guest-host interaction, hydrogen bonding, metal-ligand coordination or ionic crosslinking; or chemical and physical double crosslinking.
7. The method for preparing a granular gel material with improved strength according to claim 2, characterized in that: In step (3), the hydrogel precursor solution is a solution that can be cured to form a biocompatible hydrogel block, including a natural polymer solution (such as one or more of gelatin, sodium alginate, hyaluronic acid, cellulose and its derivatives); or a synthetic polymer solution (such as one or more of acrylamide, hydroxyethyl methacrylate); or a mixed solution of the natural polymer solution and the synthetic polymer solution. After the precursor solution is mixed with the particle gel, it is filled in the nano-micron fiber scaffold and polymerized to form an integral material.
Citation Information
Patent Citations
Composite scaffold material based on electrospinning yarn and hydrogel and preparation method thereof
CN108175874A
A method for preparing highly absorbent 3D nanofiber aerogels by electrospinning and the resulting materials
CN108404823B